Development of control laws of unmanned aerial vehicles for performing group flight at the straight-line horizontal flight stage - Barabash, Oleg; Kyrianov, Artemii (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article proposes an improved approach to controlling groups of unmanned aerial vehicles (UAVs) aimed at increasing the overall efficiency and flexibility of the control process. The use of a heterogeneous external field, which varies both in magnitude and direction, allows achieving greater adaptability and accuracy in controlling a group of UAVs. A vector field for unmanned aerial vehicles determines the direction and intensity of the vehicles' movement in space. Such vector fields can be used to develop UAV control laws, including determining optimal flight paths, controlling speed, avoiding obstacles, and ensuring coordination of a group of UAVs. The subject of the study is the methods of controlling groups of autonomous UAVs, where each vehicle may have different speeds and flight directions. To solve this problem, various methods of using a heterogeneous field have been developed and proposed. Instead of using a homogeneous field that provides a constant flight speed, a vector field is used that adapts to different conditions and characteristics of the vehicles in the group. This method allows for effective group management, ensuring the necessary coordination and interaction between the vehicles. An analysis of recent research and publications in the field of autonomous system control indicates the feasibility of using machine learning, vector fields, and a large amount of data to successfully coordinate the movement of autonomous systems. These approaches make it possible to create efficient and reliable control systems. The aim of the study is to develop laws for controlling the movement of a group of autonomous unmanned aerial vehicles at the stage of straight-line horizontal flight based on natural analogues to improve the efficiency and reliability of their coordinated movement in different conditions. The main conclusions of the research are that the proposed method of controlling groups of UAVs based on a heterogeneous field can be implemented. It takes into account a variety of vehicle characteristics and environmental conditions that are typical for real-world use scenarios. This work opens up prospects for further improving the management of UAV groups and their use in various fields of activity. The article emphasises the relevance of technology development for autonomous unmanned systems, especially in the context of autonomous transport systems.

В статті пропонується удосконалений підхід до управління групами безпілотних літальних апаратів (БПЛА), що спрямовано на підвищення загальної ефективності та гнучкості процесу управління. Використання неоднорідного зовнішнього поля, яке змінюється як за величиною, так і за напрямом дозволяє досягти більшої адаптивності та точності в управлінні групою БПЛА. Векторне поле для безпілотних літальних апаратів визначає напрямок та інтенсивність руху апаратів у просторі. Такі векторні поля можуть бути використані для розробки законів управління БПЛА, включаючи визначення оптимальних шляхів руху, керування швидкістю, уникнення перешкод та забезпечення координації групи БПЛА. Предметом дослідження є методи управління групами автономних БПЛА, де кожен апарат може мати різну швидкість та напрямки польоту. Для вирішення цієї проблеми розроблено та запропоновано різні методи використання неоднорідного поля. Замість використання однорідного поля, яке забезпечує постійну швидкість польоту, використовують векторне, яке адаптується до різних умов і характеристик апаратів у групі. Цей метод дозволяє ефективно керувати групою, забезпечуючи необхідну координацію та взаємодію між апаратами. Аналіз останніх досліджень та публікацій у галузі управління автономними системами вказує на доцільність використання машинного навчання, векторних полів та великої кількості даних для успішної координації руху автономних систем. Дані підходи дозволяють створити ефективні та надійні системи управління. Метою дослідження є розробка законів управління руху групи автономних безпілотних літальних апаратів на етапі прямолінійного горизонтального польоту на основі природних аналогів для підвищення ефективності та надійності їх координованого руху в різних умовах. Основними висновками досліджень є те, що запропонований метод управління групами БПЛА на основі неоднорідного поля може бути реалізованим. Він враховує різноманітність характеристик апаратів та умов довкілля, що є типовими для реальних сценаріїв використання. Ця робота відкриває перспективи для подальшого вдосконалення управління групами БПЛА та їх використання в різних сферах діяльності. В статті підкреслюється актуальність розвитку технологій для автономних безпілотних систем, особливо в контексті автономних транспортних систем.
Розробка законів управління безпілотними літальними апаратами для виконання групового польоту на етапі прямолінійного горизонтального польоту
Keywords: unmanned aerial vehicles; group flight; control of autonomous systems; Lyapunov vector fields; neural networks; autopilot technologies; безпілотні літальні апарати; груповий політ; управління автономними системами; векторні поля Ляпунова; нейронні мережі; технології автопілоту